Analysis of the Carrying Capacity of Settlement Land in Tamanggung District - Nurfatimah Nurfatimah (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Tamanggung District is an area development that has characteristics of agricultural land use. The development of Tamanggung District indirectly has an influence on the population and the need for residential land. This sub-district is growing very fast due to strategic area conditions, good infrastructure, adequate facilities and easy accessibility. The creation of good infrastructure tends to have an impact on increasing activity and space density. The development of settlements in Tamanggung District occurs rapidly without being matched by an increase in basic service facilities. The development of settlements causes an increase in building density (building disinfection). The density of this building causes pressure on residential land and it is feared that it can exceed the carrying capacity limit. The purpose of this study is to calculate the carrying capacity of residential land in Tamanggung District and calculate the optimal population carrying capacity of settlements. The results of the study of the carrying capacity of residential land in Tamanggung District still have land large enough to accommodate the existing population of 4 (four) times the current population. Based on the provisions of the carrying capacity of land for settlements, the DDPm of Tamanggung District is included in the category of DDP> 1 which indicates that the Tamanggung District is able to accommodate residents to live. Based on the results obtained from the calculation of the carrying capacity of residential land in Tamanggung District, if the population increases 4 times from the current population, which is 319,024 people, the available land is still able to accommodate residents in the Tamanggung District area.The content of the abstract, between 150-200 words, just one paragraph. Apparently, for the sake of simplicity, use the same language you use in your writing. Use the Abstract Fill style for this format. If you use this template correctly, all numbering will be generated automatically. So you don't need to edit it manually. Of course, if you create a section of this paper that requires numbering after this template, that number will be followed by the existing section number. Again you don't need to edit the part numbers, because if the contents of this template are deleted, the numbers will be sorted automatically. If you want to try deleting the contents of this template, please backup it first.